Landlines, Cellular, and Internet Protocol Subscribership - Snyman, Johannes H. (Journal of Strategic Innovation and Sustainability, 2021)
This research study is about the current subscriber status of the three dominant telephone technologies: landline, cellular, and Internet Protocol. After a brief history of the three technologies, data from the Federal Communication Commission (FCC) was used to determine the number of subscribers from 1997 to 2018, the last date of published data. Results indicate that landline subscribers are in steep decline. However, a complete shut-down of the system is not in sight yet. The number of cellular telephone subscribers is still growing steadily and growth is predicted to continue. The number of Internet Protocol subscribers has been growing fast but due to increased competition will begin to slow down in the future.